2020
DOI: 10.1101/2020.12.22.424003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paired SARS-CoV-2 Spike Protein Mutations Observed During Ongoing SARS-CoV-2 Viral Transfer from Humans to Minks and Back to Humans

Abstract: A mutation analysis of a collection of SARS-CoV-2 genomes around the world via sequence, date, geographic location, and species has revealed a large number of variants from the initial reference sequence in Wuhan. It also reveals that humans infected with SARS-CoV-2 have infected mink populations in the Netherlands, Denmark, United States, and Canada. In these animals, a small set of mutations often in combination, in the spike protein receptor binding domain (RBD) has apparently transferred back into humans. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The N501Y mutation is responsible for a high infectivity and transmissibility of the Alpha variant of SARS-CoV-2 (64) and has the largest stabilizing effect in our dataset (Table 1). The N501T mutation found in the SARS-CoV-2 variants transmitted from mink to humans (65, 66) occurs at the same position. Analysis of FEP trajectories reveals that the stabilization effect associated with N501Y and N501T mutations is due to substitution of the asparagine with less polar side chains of tyrosine and threonine.…”
Section: Resultsmentioning
confidence: 95%
“…The N501Y mutation is responsible for a high infectivity and transmissibility of the Alpha variant of SARS-CoV-2 (64) and has the largest stabilizing effect in our dataset (Table 1). The N501T mutation found in the SARS-CoV-2 variants transmitted from mink to humans (65, 66) occurs at the same position. Analysis of FEP trajectories reveals that the stabilization effect associated with N501Y and N501T mutations is due to substitution of the asparagine with less polar side chains of tyrosine and threonine.…”
Section: Resultsmentioning
confidence: 95%
“…193,[195][196][197] Studies have demonstrated the high transmission among mink through direct contact or airborne, accompanied by adapted mutations. [198][199][200][201][202] Notably, the transmission can cause the "back to human" infection and subsequently leads to the prevalence among humans. 198,202,203 Therefore, measures of prevention and control should be tailored to avoid the potential large-scale community transmission, regarding the impact of mutants on viral fitness pathogenicity and contagiousness between mink and humans.…”
Section: Minkmentioning
confidence: 99%
“…[198][199][200][201][202] Notably, the transmission can cause the "back to human" infection and subsequently leads to the prevalence among humans. 198,202,203 Therefore, measures of prevention and control should be tailored to avoid the potential large-scale community transmission, regarding the impact of mutants on viral fitness pathogenicity and contagiousness between mink and humans. Intranasal inoculation of SARS-CoV-2 induces robust replication of virus in upper and lower respiratory tract, including nasal turbinate, tonsil, soft palate, and trachea, and in lung tissue with peaking on 2 dpi and persisting until 8 dpi before dropping below detection limits on 14 dpi.…”
Section: Minkmentioning
confidence: 99%
“…Outbreaks of SARS-CoV-2 in mink farms in several countries, including the Netherlands, Denmark, USA and Canada, and evidence of zoonotic and anthroponotic transmission in such cases 16 have raised concern regarding the associated animal and human infection risks, including with ferrets kept as pets, working animals or in research, particularly in high-density settings. 17 The APHA has issued guidance for ferret owners and veterinarians on enhanced precautionary biosecurity measures, including a 21-day isolation period for ferrets in Covid-19 self-isolating households or ferrets testing positive for SARS-CoV-2 or brought to the UK from countries outside current travel corridor lists.…”
Section: Infection and Clinical Signsmentioning
confidence: 99%